2012
DOI: 10.1200/jco.2012.30.4_suppl.605
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in outcomes for early-stage colon cancer.

Abstract: 605 Background: Retrospective analyses of clinical trials suggest that gender may influence the risk of recurrence and survival in patients diagnosed with early stage colon cancer. Whether this association persists in the setting of routine clinical practice is unclear. Our aims were to 1) assess for gender differences in outcomes in early stage colon cancer and 2) evaluate if the effect of gender on outcomes is modified by adjuvant therapy (AT). Methods: Using a population-based cohort of patients diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Also as discussed earlier there is more incidence of signet and Mucinous carcinoma in younger patients and greater proportion of cases arising in ulcerative colitis comparing sex of the patient with stage of tumor it was seen that the maximum number of males presented with stage III, while stage II was predominant amongst females. Griffin et al and Alipour et al [34,35] studied various predictors of survival in colorectal cancer and evaluated that for a given age and stage, females had better outcome than males which was reflected in our study too.…”
Section: Resultssupporting
confidence: 59%
“…Also as discussed earlier there is more incidence of signet and Mucinous carcinoma in younger patients and greater proportion of cases arising in ulcerative colitis comparing sex of the patient with stage of tumor it was seen that the maximum number of males presented with stage III, while stage II was predominant amongst females. Griffin et al and Alipour et al [34,35] studied various predictors of survival in colorectal cancer and evaluated that for a given age and stage, females had better outcome than males which was reflected in our study too.…”
Section: Resultssupporting
confidence: 59%
“…7,[12][13][14][15][16][17][18][19] Pooled analysis of OS showed a significant difference between women and men with slight heterogeneity in a fixed effects model(HR 5 0.87, 95% CI: 0.85-0.89, p < 0.00001; I 2 5 26%, p 5 0.22, Fig. Overall survival (OS) was significantly longer in female patients than male patients with colorectal cancer, as reported in the nine included studies.…”
Section: Main Results Heterogeneity and Sensitivity Analysismentioning
confidence: 86%
“…Overall survival (OS) was significantly longer in female patients than male patients with colorectal cancer, as reported in the nine included studies. 7,[12][13][14][15][16][17][18][19] Pooled analysis of OS showed a significant difference between women and men with slight heterogeneity in a fixed effects model(HR 5 0.87, 95% CI: 0.85-0.89, p < 0.00001; I 2 5 26%, p 5 0.22, Fig. 2).…”
Section: Main Results Heterogeneity and Sensitivity Analysismentioning
confidence: 99%
“…Our analysis showed no significant association between sex and survival; however, conflicting data have been reported in the literature. Some studies reported that the female sex is associated with better survival, while others showed no difference [ 5 , 17 , 18 , 19 ]. Different variables, such as region and limited sample size, can explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%